Rola pontyfikatu Cyryla (412-444) w procesie umacniania potęgi patriarchy aleksandryjskiego w Kościele wczesnobizantyńskim - Hołasek, Andrzej (Vox Patrum, 2012)
The author analyzes the content of Historia Ecclesiastica (Church History) by Socrates Scholasticus as well as the documents contained in the series Acta Conciliorum Oecumenicorum to depict political conditions of the pontificate of Bishop Cyril of Alexandria (412-444). In the article the scholar shows the ways in which Cyril’s actions influenced reinforcing of the Egyptian Patriarchate position in the Eastern Church. From the first years of his pontificate Cyril was very knowledgeable about political situation at the imperial court in Constantinople. Juvenile Theodosius was influenced by her older sister Pulcheria and changing prefects at her side. Court coteries fought each other to win the regentess’ favour. The Court performed anti-Jewish and antipagan policy. Cyril took advantage of it to get rid of his serious opposition. He expelled Jews from the city and led to killing of a woman-philosopher Hypatia, who centered the pagan establishment around her. He also crushed prefect Orestes, who acted against his tyranny. The situation has changed in 428. Emperor Theodosius grew up and began to make their own decisions. The monks of Egypt came to the capital to lodge a complaint about Cyril to the Emperor. Theodosius designated Nestorius, the Bishop of Constantinople, to investigate the complaint. It seriously threatened to the Egyptian patriarch with loss of his rank and of being hound out of the country. At the same time Nestorius supported calling the mother of Jesus Christ with the name Theothokos. Cyril decided to use this fact to accuse the bishop of heresy. It was his way of diverting the public attention from the charges against himself. In the article the author, basing on source materials, strives to prove that all Cyril’s moves arose due to his determination to retain his position to date. Theological issues were of secondary importance to him. He had no scruples in accomplishing his goals. Violence, bribery, propaganda, instigating and inciting the people of Ephesus were his methods. Cyril managed to defeat Nestorius thanks to his flair for politics and tracking current information. Cyril’s activities not only strengthened the position of Egyptian patriarchate in the eastern church but also led to gain a temporary control over the Constantinople bishopric, as Maximianus, Nestorius successor, was a henchman of the Bishop of Alexandria.